1995
DOI: 10.1093/infdis/172.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Class and Subclass Responses to Pneumococcal Polysaccharides following Immunization of Human Immunodeficiency Virus-Infected Patients

Abstract: Antibodies of the IgM class and IgG2 and IgA2 subclasses are prominent in responses to pneumococcal polysaccharides (PPS) but may be decreased in human immunodeficiency virus (HIV)-infected patients, among whom invasive pneumococcal disease is common. After immunization of HIV-infected and -seronegative subjects with pneumococcal vaccine, the number of PPS-specific antibody-secreting cells (ASC) producing IgM was significantly lower among HIV-infected subjects, whereas PPS-specific IgG and IgA ASC were more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 32 publications
6
38
0
1
Order By: Relevance
“…Furthermore, even children older than 2 years who have HIV infections and were vaccinated with the 23vPPV did not respond well to the polysaccharide antigen, when compared with controls. 16 Just six children were more than 2 years old at the time of data collection and none of them had been given the 23vPPV, already available at that time, confirming the published data that states that selective vaccination of high-risk groups is less efficient than vaccination of all children.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, even children older than 2 years who have HIV infections and were vaccinated with the 23vPPV did not respond well to the polysaccharide antigen, when compared with controls. 16 Just six children were more than 2 years old at the time of data collection and none of them had been given the 23vPPV, already available at that time, confirming the published data that states that selective vaccination of high-risk groups is less efficient than vaccination of all children.…”
Section: Discussionsupporting
confidence: 71%
“…200 cells/mL after receipt of HAART and for those patients who have undergone pneumococcal polysaccharide vaccination 5 years earlier [13]. However, most studies conducted in patients not receiving HAART suggest that HIV-infected patients have a significantly lower frequency and magnitude of antibody response to vaccination with 23-valent PPV than those without HIV infection, and antibody titres [immunoglobulin G (IgG) or IgM] appear to be associated with CD4 cell count and decrease more rapidly in HIV-infected patients [14][15][16][17][18][19][20][21][22]. Interpretation of studies conducted in the HAART era is limited by different durations of and immunological and virological responses to HAART, different vaccination schedules and short-term observation of antibody responses [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating short-term serological responses to 23-valent PPV in HIV-infected patients have not produced consistent results [14][15][16][17][18][19][20][21][22][24][25][26][27][30][31][32][33][34][35][36][37][38], and only one study assessed the rate of antibody decline for five consecutive HAART, highly active antiretroviral therapy; MSM, men who have sex with men; PVL, plasma HIV RNA load; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that up to a third of serum antibodies that are reactive with the polysaccharide capsule of an invasive mucosal Gram-positive organism, Streptococcus pneumoniae, are of the IgA class (14,15). The majority of this pathogen-specific IgA in serum is in the polymeric form (≥ 2 IgA molecules bound by a J chain) and remains polymeric long after immunization or infection (15), even though about 90% of the total IgA in serum is in the monomeric form (5).…”
Section: Introductionmentioning
confidence: 99%
“…S. pneumoniae may colonize the nasopharyngeal mucosa without sequelae but also commonly causes serious invasive clinical syndromes, including pneumonia, bacteremia, and meningitis in children and adults (16)(17)(18)(19). Natural infection and immunization elicit capsule-specific polymeric IgA (pIgA) responses in blood and at mucosal sites (14,15,(20)(21)(22). Thus, pIgA may play a functional role at both mucosal and systemic sites.…”
Section: Introductionmentioning
confidence: 99%